Analysis of immunostaining and western blotting of endothelin 1 and its receptors in mitral stenosis - Leão,Sydney Correia (2015)
AbstractIntroduction:Rheumatic Fever represents a serious public health problem in developing countries, with thousands of new cases each year. It is an autoimmune disease, which occurs in response to infection by streptococcus A.Objective:The aim of this study was to evaluate the immunolabeling and protein expression for endothelin-1 and 3 (ET-1, ET-3) and its receptors (ETA, ETB) in rheumatic mitral valves.Methods:Immunohistochemistry was used to identify ET-1/ET-3 and ETA/ETB receptors in rheumatic and control mitral valves. Quantitative analysis of immunostaining for ET-1/ET-3 and ETA/ETB receptors was performed. In addition, western blot analysis was carried out to assess protein levels in tissue samples.Results:ET-1 and ETA receptor immunostaining predominated in stenotic valves, mainly associated with fibrotic regions, inflammatory areas and neovascularization. Quantitative analysis showed that the average area with positive expression of ET-1 was 18.21±14.96%. For ETA and ETB, the mean expressed areas were respectively 15.06±13.13% and 9.20±11.09%. ET-3 did not have a significant expression. The correlation between the expression of both endothelin receptors were strongly positive (R=0.74, P=0.02), but the correlation between ET-1 and its receptor were negative for both ETA (R=-0.37, P=0.25), and ETB (R=-0.14, P=0.39). This data was supported by western blot analysis.Conclusion:The strong correlation between ET-1 and its receptors suggests that both play a role in the pathophysiology of rheumatic mitral valve stenosis and may potentially act as biomarkers of this disease.